(untitled) (Cardiovascular Journal, 2019)
Background: Mitral stenosis is often present with pulmonary hypertension. Closed Mitral Commissurotomy (CMC) is a treatment of choice for severe mitral stenosis. In this study, we examined the per-operative changes of pulmonary artery pressure following opening of stenosed mitral valve. Methods: All these CMCs were performed routinely through the left antero-lateral thoracotomy (4th intercostal space) and dilatation was done by metallic Tubb’s Dilator. Peroperative left atrial and Pulminary Arterial pressures were measured before and after dilatation. Results: 15 patients had undergone CMC. Following CMC, per-operative mean Pulmonary artery pressure was reduced from 45.5±7.1 mm of Hg to 39.0±8.8 mm of Hg (p=0.043). Mean left atrial pressure reduced from 35.9±5.6 mm of Hg to 30.0±9.1 mm of Hg (p = 0.049). At three months follow up after closed mitral commissurotomy mitral valve area at echocardiography was found 2.29±0.18 cm2. There was no case of death after closed mitral commissurotomy. Mild mitral regurgitation occurred in 1 patient. Conclusion: We conclude that there is immediate significant reduction of pulmonary Artery pressure following closed mitral commissurotomy. This reduction is apparently comparable with a similar reduction of left atrial pressure. Cardiovasc. j. 2019; 11(2): 147-151